Renal cortical volume: High correlation with pre- and post-operative renal function in living kidney donors. Issue 99 (February 2018) - Gardan, Edouard; Jacquemont, Lola; Perret, Christophe; Heudes, Pierre-Marie; Gourraud, Pierre-Antoine; Hourmant, Maryvonne; Frampas, Eric; Limou, Sophie
Highlights: CT scan vs. scintigraphy kidney function measures at pre- and 1-year post-donation. Renal volume is significantly correlated with pre-donation split renal function. Preserved kidney volume is strongly correlated with post-donation kidney function. Cortical volume (RCoV) is the most accurate metrics to predict kidney function. RCoV is a pertinent surrogate to scintigraphy for pre-donation clinical evaluation. Abstract: Background: CT volumetry has previously been proposed as an alternative to scintigraphy for the evaluation of pre-donation split renal function and the prediction of post-donation renal function in living kidney donors. The aim of our study was to retrospectively assess the relevance of three CT volumetry techniques for estimating pre-donation kidney function and predicting the risk for chronic kidney disease (CKD) at 1-year post-nephrectomy in a French cohort of living donors using isotopic measures of kidney function. Methods: Kidney volume was quantified pre-donation for 105 donors using three methods total parenchymal three-dimensional renal volume (3DRV), total parenchymal renal volume contouring (RVCt), and renal cortical volume (RCoV). Subjects also had a 51Cr-EDTA scintigraphy to measure glomerular filtration rate (mGFR) pre-donation and 1-year after donation. For each volume, we tested for association with mGFR using univariate regression models, and computed receiver operating characteristics analyses to assess their predictive potential of post-donation CKD. Results: Our population was composed of healthy subjects, who were predominantly female (69%) with a median age at donation of 51yo. Median mGFR was 102 mL/min/1.73 m 2 at pre-donation and 66 mL/min/1.73 m 2 1-year after nephrectomy. The pre-donation median volume of the preserved kidney was 156 cm 3, 163 cm 3 and 99 cm 3 for the 3DRV, RVCt and RCoV methods respectively, with a high correlation observed between each technique (R > 0.84). For all methods, total kidney volume was significantly associated with pre-donation mGFR (P < 0.001). Preserved kidney volume was also strongly correlated with post-donation mGFR (P < 0.0001), with the strongest correlation observed for RCoV (R = 0.60 vs. R = 0.39 and R = 0.51 for 3DRV and RVCt, respectively). Finally, the RCoV method yielded the best predictive value of 1-year post-donation CKD (AUC = 0.80 vs. AUC = 0.76 and 0.70 for RVCt and 3DRV, respectively). Conclusions: In our cohort of healthy donors with measured kidney function, cortical volumetry (RCoV) appears as the best volumetric technique to use as a surrogate to scintigraphy for estimating pre-donation split renal function and predicting post-donation renal outcomes.